2002
DOI: 10.1038/ncb800
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Morgue is an F box/ubiquitin conjugase domain protein important for grim-reaper mediated apoptosis

Abstract: In Drosophila melanogaster, apoptosis is controlled by the integrated actions of the Grim-Reaper (Grim-Rpr) and Drosophila Inhibitor of Apoptosis (DIAP) proteins (reviewed in refs 1 4). The anti-apoptotic DIAPs bind to caspases and inhibit their proteolytic activities. DIAPs also bind to Grim-Rpr proteins, an interaction that promotes caspase activity and the initiation of apoptosis. Using a genetic modifier screen, we identified four enhancers of grim-reaper-induced apoptosis that all regulate ubiquitination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 33 publications
1
107
0
Order By: Relevance
“…It should be noted that a role has been suggested for Morgue in promoting the degradation of DIAP1, although it has not been shown that it serves as its ligase. 42,43 Also, a recent study demonstrates that phosphorylation of DIAP1 by the Drosophila IKK-related kinase leads to its destruction under nonapoptotic conditions. 44 Thus, it appears that multiple pathways and mechanisms regulate the IAP group of proteins that are positioned in a critical cross roads along the developmental and apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a role has been suggested for Morgue in promoting the degradation of DIAP1, although it has not been shown that it serves as its ligase. 42,43 Also, a recent study demonstrates that phosphorylation of DIAP1 by the Drosophila IKK-related kinase leads to its destruction under nonapoptotic conditions. 44 Thus, it appears that multiple pathways and mechanisms regulate the IAP group of proteins that are positioned in a critical cross roads along the developmental and apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] In GMR-reaper eye imaginal discs, DIAP1 degradation is very prominent in cells immediately posterior to the column of R8 photoreceptor neurons, which are very resistant to apoptosis 52 and where DIAP1 is not degraded (Figure 7a and b; R8 photoreceptor columns are marked by arrows; the zones of DIAP1 degradation by asterisks (*)). Interestingly, reduced DrICE activity in heterozygous loss-of-function alleles partially protects DIAP1 from reaper-induced degradation (Figure 7c and d), which is consistent with the suppression of GMR-reaper by these alleles (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…47 If reaper is in excess, it triggers degradation of DIAP1 (Figure 7b) and thus apoptosis. [16][17][18][19][20] Therefore, owing to the failure of DIAP1 to bind to the class C subunit, the wt/ class C heterotetramer may shift the equilibrium towards binding of DIAP1 to reaper such that DIAP1 is more efficiently degraded by reaper, resulting in higher enzymatic activity of the wt/class C heterotetramer. Consistent with this notion, reduced DrICE activity in heterozygous loss-of-function alleles partially protects DIAP1 from reaper-induced degradation (Figure 7c and d), whereas the class C alleles of DrICE fail to protect DIAP1 from degradation (Figure 7e and f), suggestive of decreased binding of the wt/class C heterotetramer to DIAP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first pulse triggers midgut cell death and differentiation of the cen-tral nervous system, the second triggers salivary gland autophagic cell death through the activation of a set of early ecdysone responsive genes namely Broad Complex (BR-C), E74A and E75 (Burtis et al, 1990;DiBello et al, 1991;Jiang et al, 1997;Lee and Baehrecke, 2001;Seagraves and Hogness, 1990;Thummel, 2001). Early genes, in turn, induce the transcriptional activation of late genes, including Drosophila cell death genes reaper (rpr), head involution defective (hid), and grim (Cristich et al, 2002;Goya et al, 2000;Greether et al, 1995;Srinivasula et al, 2002;White et al, 1994;Wing et al, 2002). Also, in response to the second hormonal pulse, the transcription of the stage-specific gene E93 is induced.…”
Section: Introductionmentioning
confidence: 99%